(Des)movilización de la sociedad civil chilena post-trauma, gobernabilidad y neoliberalismo (1990-2010) - Jara Ibarra, Camila (Ariadna Ediciones, 2019)
Research on the Chilean social mobilization of the last decades, the exhaustion of the neoliberal model and the search for alternatives